IMPLIKASI UNDANG-UNDANG DESA TAHUN 2014 TERHADAP TATA KELOLA DAN PARTISIPASI DEMOKRASI - Rizki Dwi Pangestu (PERAHU (PENERANGAN HUKUM) : JURNAL ILMU HUKUM, 2026)
Village governance, as the level of government closest to the community, plays a crucial role in strengthening democracy in Indonesia. Law Number 6 of 2014 on Village Governance has significantly transformed the governance paradigm by granting greater authority to local communities. This study aims to examine the implications of the law on community perceptions and democratic participation in Rahong Village, Malingping District, Lebak Regency. This research employs an empirical juridical approach with qualitative methods, focusing on community attitudes and behaviors toward the implementation of the law. The findings indicate that the law has a positive impact on community perceptions of the quality of village governance and encourages greater participation in democratic processes. Nevertheless, several challenges remain, including limited institutional capacity, lack of transparency, and issues of accountability. These findings provide important insights for the formulation of more effective policies aimed at strengthening democracy at the village level in Indonesia.